Towards the praxis of a sustainable knowledge‑based economy - Klimska, Agnieszka (Studia Ecologiae et Bioethicae, 2016)
Various presentations of the current strategies for economic development increasingly stress the need to abandon the existing model of economy, its redefinition and the necessity to develop a new concept of knowledge-based economy (KBE). Consequently, knowledge is attributed an essential role in stimulating socio-economic development, including also sustainable development. The direction of changes designated by the development of knowledge- -based economy, however, carries with it a number of challenges that must be dealt with and which are gradually being included in numerous sustainable development strategies. Similarly, implementation of certain visions of sustainable development generates the need to make specific assumptions, different from the guidelines defined for the mainstream economy (e.g. taking into account global modelling and system analysis or the law of entropy) (Czaja 2011: 164). Implementation of the preferred directions of development, requires not so much efficient, but proper management, i.e. one which would translate itself onto the plane of decision-making and, subsequently, that of application. Management processes, including management of sustainable development which draws on the principles of a knowledge-based economy, require also taking into account those factors that can really support the sphere of praxis and hence help to shape a knowledge-based society. This article aims at examining the relationship between a knowledge-based economy and the concept of sustainable development, especially in relation to its economic implications. It will, moreover, concentrate on the assessment of practical functioning of a sustainable knowledge-based economy which constitutes an important development strategy in the process of shaping an information society.